Confessions ebook - Minato, Kanae (2014)
In this international bestselling thriller, a former teacher delivers her final lesson to her students—including the two children that murdered her daughter. After calling off her engagement in the wake of a tragic revelation, Yuko Moriguchi had nothing to live for except her only child, four-year-old child, Manami. Now, following an accident on the grounds of the middle school where she teaches, Yuko has given up and tendered her resignation. But first she has one last lecture to deliver. She tells a story that upends everything her students ever thought they knew about two of their peers, and sets in motion a diabolical plot for revenge. Narrated in alternating voices, with twists you'll never see coming, Confessions probes the limits of punishment, despair, and tragic love, culminating in a harrowing confrontation between teacher and student that will place the occupants of an entire school in danger. You'll never look at a classroom the same way again.